The effect of lipoic acid and vitamin E on rat brain: An FTIR spectroscopic approach - Akkas, SB; Yilmaz, O; Severcan, F (Biophysical Society, 2005)
[Abstract Not Available]
49th Annual Meeting of the Biopysical-Society -- FEB 12-16, 2005 -- Long Beach, CA